P-245 Now where is that policy on …. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Powell, Paula; Monnery, Daniel; Schofield, Susan; Hyland, Charles; Jones, Debbie
Abstract : Most specialist palliative care units have clinical policies to support best practice. In addition multiple resources are available to clinical staff as books, clinical guidelines and apps. Our experience at Willowbrook Hospice was that staff would refer to guidelines and formats they were most familiar with even if newer versions were available. Equally comprehensive policies were not referred to because staff could not recall how to find them or when found the pertinent information was not easily accessible. This represents a risk to patients and the organisation. This poster describes the work that the medical and nursing teams carried out to develop hospice specific 'quick reference guidelines' for important policies and procedures that distilled the information into an accessible form, usually flow charts. Examples are – hypercalcaemia management, commencing ketamine, recognition and management of delirium and sepsis. Over a year this has developed into a comprehensive but easily accessible practice guide that staff know is easily available on their desktops and in paper format in a ward folder. As new policies are updated a 'quick reference' guide is created and added to the resource. This change has been supported by education as each topic is added so all staff are aware of changes to clinical practice and how to access the most up to date information.